Análise estrutural do pericarpo e da semente de três espécies de Phoradendron Nutt. (Viscaceae) - Polli, Anderson (2013)
Among angiosperms, a few plant families, as Viscaceae, developed the parasitic habit. Phoradendron Nutt., genus included in this family, comprises aerial hemiparasites plants, chlorophyllated, preferentially found at the top canopy of the host plant. Associated with parasitism, the presence of unisexual flowers, absence of seed coat in seeds, simplifying the gynoecium and the formation of viscous mass in the pericarp of the fruit, are factors of evolutionary convergence, since they are related to forms of propagation of these species. Phoradendron is particularly well represented in the American continent, and is commonly referred to as "birdie herb" because its fruits are eaten and spread by frugivorous birds. Given, therefore, the botanical and ecological importance and the need for studies of ontogeny of the reproductive organs of these parasitic plants, the present research aimed the structural analysis of the pericarp and seed in development of three species - Phoradendron dipterum (Kunth) Trel.; P. quadrangulare (Kunth) Grisebach.; P. piperoides (Kunth) Trel. - with the purpose of contributing to the characterization of species / alliances and defining the type of fruit. The botanical material collected was processed by usual techniques for analysis by light microscopy and scanning electron microscopy. The three species have fruit sourced from infer ovary, whose wall is formed by external uniseriate epidermis, mesophyll differentiated into three distinct histological zones, two of nature and parenchymatous, region viscina precursor layer, which shows evidence of cell division in different planes. The inner epidermis is slightly distinguishable, consisting of cells with variable outline, thin walls, which may undergo periclinal division. In the pericarp differentiation a few structural changes occur, being changes in the middle layers mainly verified, composing two regions, one of parenchymatous nature, and the other one which differs in viscina layer. The ripe fruit consists of epidermal exocarp, external parenchymatous mesocarp with druses and sclereids, middle and inner mesocarp with parenchyma more or less compressed, and viscina layer; the endocarp is collapsed. According to the source infer, the fruit should be seen as a subtype of pomaceous. The vascularization of the fruit is made by collateral vascular bundles distributed in two rings, and can occur in internal beams reversed. The three species have seed no integument, originated from a single egg and reduced tenuinucellate. In turn, the mature seed endosperm and embryo chlorophyllous has already differentiated. In the endosperm, uniseriate epidermis and parenchymatous tissue are distinguishable, whose cells are polyhedral of variable outline, with chloroplasts and visible starch content; in this organelle, idioblasts with druses may occur. The embryo is straight, with hypocotyl-root axis relatively short and free from the endosperm, plumule is not evident and two cotyledons are reduced. The fruits and seeds of the three species are structurally similar with a few differentiable characters.